“Post-Decompressive Neuropathy”: New-Onset Post-Laminectomy Lower Extremity Neuropathic Pain Different from the Preoperative Complaint - Lorraine A. T. Boakye (Asian Spine Journal, 2018)
Study Design Level III retrospective cross-sectional study. Purpose To define and characterize the presentation, symptom duration, and patient/surgical risk factors associated with ‘postdecompressive neuropathy (PDN).’ Overview of Literature PDN is characterized by lower extremity radicular pain that is ‘different’ from pre-surgical radiculopathy or claudication pain. Although it is a common constellation of postoperative symptoms, PDN is incompletely characterized and poorly understood. We hypothesize that PDN is caused by an intraoperative neuropraxic event and may develop early (within 30 days following the procedure) or late (after 30 days following the procedure) within the postoperative period. Methods Patients who consented to undergo lumbar laminectomy with or without an instrumented fusion for degenerative lumbar spine disease were followed up prospectively from July 2013 to December 2014. Relevant data were extracted from the charts of the eligible patients. Patient demographics and surgical factors were identified. Patients completed postoperative questionnaires 3 weeks, 3 months, 6 months, and 1 year postoperatively. Questions were designed to characterize the postoperative pain that differed from preoperative pain. A diagnosis of PDN was established if the patient exhibited the following characteristics: pain different from preoperative pain, leg pain worse than back pain, a non-dermatomal pain pattern, and nocturnal pain that often disrupted sleep. A Visual Analog Scale was used to monitor the pain, and patients documented the effectiveness of the prescribed pain management modalities. Patients for whom more than one follow-up survey was missed were excluded from analysis. Results Of the 164 eligible patients, 118 (72.0%) completed at least one follow-up survey at each time interval. Of these eligible patients, 91 (77.1%) described symptoms consistent with PDN. Additionally, 75 patients (82.4%) described early-onset symptoms, whereas 16 reported symptoms consistent with late-onset PDN. Significantly more female patients reported PDN symptoms (87% vs. 69%, p=0.03). Patients with both early and late development of PDN described their leg pain as an intermittent, constant, burning, sharp/stabbing, or dull ache. Early PDN was categorized more commonly as a dull ache than late-onset PDN (60% vs. 31%, p=0.052); however, the difference did not reach statistical significance. Opioids were significantly more effective for patients with early-onset PDN than for those with late-onset PDN (85% vs. 44%, p=0.001). Gabapentin was most commonly prescribed to patients who cited no resolution of symptoms (70% vs. 31%, p=0.003). Time to symptom resolution ranged from within 1 month to 1 year. Patients’ symptoms were considered unresolved if symptoms persisted for more than 1 year postoperatively. In total, 81% of the patients with early-onset PDN reported complete symptom resolution 1 year postoperatively compared with 63% of patients with late-onset PDN (p=0.11). Conclusions PDN is a discrete postoperative pain phenomenon that occurred in 77% of the patients who underwent lumbar laminectomy with or without instrumented fusion. Attention must be paid to the constellation and natural history of symptoms unique to PDN to effectively manage a self-limiting postoperative issue.